Hydrocarbons in Coal Deposit From Long Tutoh, Baram and Merit Pilla, Kapit of Sarawak - Norzilawatil Azwa, Mohamad (Universiti Malaysia Sarawak, UNIMAS, 2009)
The coal samples obtained from Long Tutoh coalfield, Baram and Merit Pilla coalfield, Kapit, Sarawak were studied to determine their hydrocarbon composition. The objectives of this study are (1) to characterize the organic components in two Sarawakian coal samples, (2) to predict the source of organic matters and (3) to evaluate maturity degree of coal samples through biomarker evaluation. The geolipid from the coal sample was extracted using Soxhlet extractor and subsequently being separated into aliphatic fraction and polyaromatic fraction on activated silica gel chromatography. The analysis of organic components in the coal samples were performed using capillary gas chromatography/flame ionization detector (GC/FID). Biomarker indices such as ratio of pristane to phytane (Pr/Ph), pristane to heptadecane (Pr/C17), phytane to octadecane (Ph/C18), C25/C15, C27/C17, and CPI(25-31) are used to evaluate the source of origin of organic matter and maturity of both coal samples. The CPI(25-31) values from both coal samples showed that they are thermally immature. Other biomarker indices which are Pr/Ph. Pr/C17 and Ph/C18 indicated that both coal samples were deposited under anoxic and open water condition.